2019
DOI: 10.1002/jnr.24421
|View full text |Cite
|
Sign up to set email alerts
|

Classification of cocaine‐dependent participants with dynamic functional connectivity from functional magnetic resonance imaging data

Abstract: Static functional connectivity (FC) analyses based on functional magnetic resonance imaging (fMRI) data have been extensively explored for studying various psychiatric conditions in the brain, including cocaine addiction. A recently emerging, more powerful technique, dynamic functional connectivity (DFC), studies how the FC dynamics change during the course of the fMRI experiments. The aim in this paper was to develop a computational approach, using a machine learning framework, to determine if DFC features we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 62 publications
(109 reference statements)
3
15
0
3
Order By: Relevance
“…We used several different linear modeling approaches, all of which produced highly similar model weights, predictions, and regions with high mean predictive connectivity - suggesting they learned similar information. Our accuracies also compare favorably to previous fMRI decoding studies using functional connectivity to classify drug use, in both nicotine smoking 4,7,49 and cocaine use disorder 50 - even though most studies did not test out-of-sample or featured much smaller sample sizes (both of which can inflate prediction performance). Furthermore, this is one of the first fMRI study 51 , and the largest to date, to classify chronic MJ use (i.e., cannabis use disorder) - a relatively understudied drug use disorder.…”
Section: Discussionsupporting
confidence: 61%
“…We used several different linear modeling approaches, all of which produced highly similar model weights, predictions, and regions with high mean predictive connectivity - suggesting they learned similar information. Our accuracies also compare favorably to previous fMRI decoding studies using functional connectivity to classify drug use, in both nicotine smoking 4,7,49 and cocaine use disorder 50 - even though most studies did not test out-of-sample or featured much smaller sample sizes (both of which can inflate prediction performance). Furthermore, this is one of the first fMRI study 51 , and the largest to date, to classify chronic MJ use (i.e., cannabis use disorder) - a relatively understudied drug use disorder.…”
Section: Discussionsupporting
confidence: 61%
“… Abrol et al (2019) introduced a multimodal (structural MRI and DFC) data fusion framework to predict Alzheimer’s disease progression and found a significant improvement in performance over unimodal prediction analyses. Sakoglu et al (2019) reported a higher accuracy of DFC-based classification (0.95) than that based on SFC (0.81) for the identification of cocaine dependence, suggesting the diagnostic value of DFC metrics. In the present study, we used the DFC state of each window as features to construct an optimal classifier to distinguish the LPE patients from the NCs.…”
Section: Discussionmentioning
confidence: 92%
“…This exploratory study is an investigation of temporally dynamic regional brain activation patterns underlying cue-reactivity, response-inhibition, and their interaction in individuals with MUD. While similar sliding window techniques are relatively common in dynamic functional connectivity analyses 54,55 and despite decades of evidence for temporal variation in regional sensitization and habituation in cognitive/affective neuroscience [31][32][33] , dynamic analyses of regional activation in addiction remain rare and this is the rst study which explored this dynamic interaction in response-inhibition in the context of cue-reactivity.…”
Section: Discussionmentioning
confidence: 99%